Literature Stufy Of Commercial Antioxidant Compounds Which Can Be Added To Natural Semen Extender In Pig - Reynaldy Militia Christian; Nancy D.F.K Foeh; Cynthia Dewi Gaina (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2022)
Semen dilution is carried out by adding materials that act as energy sources for spermatozoa so as to prolong the survival of spermatozoa outside the body on the condition that they can provide an energy source for spermatozoa, become a buffer or buffer, do not inhibit the movement of spermatozoa and are not toxic or toxic, and can protect spermatozoa from cold shock (cold shock). The purpose of this study was to determine what types of commercial antioxidants can be added to the cement diluent to maintain the quality of life of porcine spermatozoa. This research uses the literature study method. This literature was obtained from searching and gathering various library sources from Google Scholar with the help of the Mendeley application. Based on research results, several commercial antioxidants such asVitamin C (Ascorbic Acid), Vitamin E (Tocopherol) and Glutathione (GSH) can be added to the diluent which can bind calcium activity, as an early capitation medium and as an energy source that can protect spermatozoa from cold shock (Cold Shock). plays a role in preventing or breaking the chain reaction of lipid peroxidation to protect the plasma membrane of spermatozoa so that it can maintain the life of spermatozoa during storage for a longer time.